Motivation, Work Environment, and Training and Development Determine the Effect Employee Performance (A Study of Human Resource Management Literature Review) - Naryanto; Herni Pujiati (Dinasti International Journal of Digital Business Management, 2025)
This study focuses on the determine the effect of motivation, work environment, and training and development on employee performance in various organizations. The aim of this research is to analyze the contributions of these three variables in enhancing employee performance within the context of human resource management. The method used is a literature review, where the researcher collects and analyzes various relevant articles and previous studies. The results indicate that strong motivation, a positive work environment, and effective training and development programs significantly improve employee performance. These three variables are interrelated and have a crucial impact on productivity and overall organizational performance.